Analisis Parameter Kompresi Algoritma Elias Omega Code dan Fibonacci Code Pada File Digital - Ibrahim Hasan; Tommy Tommy; Nenna Irsa Syahputri (UIN Sumatera Utara, 2021)
The need for greater storage capacity is the cause of the emergence of various compression techniques.By compressing, large data will be reduced in size so as to save storage capacity. In this research, usingthe Elias Omega Code and Fibonacci Code algorithms, the performance will be measured with the ratioof compression, compression ratio and space saving in digital text files. Compression is done by readingthe string in a digital text file, then the Elias Omega Code algorithm and the Fibonacci Code algorithmcreate a string code and perform the compression process. From the final result of the compression,files with extension * .EB and * .FB contain character information and Bit String from the compressionresult that can be decompressed. From the output of the decompression is the original digital text filethat is saved with the file extension * .txt. In testing this system, a sample is used, namely a stringconsisting of one type of character stored in a digital text file with the extension * .txt. From thecompression process on digital file character strings, the Fibonacci Code algorithm is superior in termsof compression ratio of compression with an average of 1.72, compression ratio with an average of 57%and space saving of an average of 42%.Keywords: analysis, compression, text, Elias Omega Code, Fibonacci Code